ANALISIS NILAI TAMBAH DAN STRATEGI PENGEMBANGAN USAHA PENGOLAHAN SUSU SAPI PERAH BEST COW PADA UNIT PRODUKSI KOPERASI PETERNAK GALUR MURNI DI KECAMATAN AJUNG KABUPATEN JEMBER - Roh Mayana Girsang; Titin Agustina (UPT Penerbitan Universitas Jember, 2018)
Best Cow is a cow milk processing industry to provide value to milk aimed at obtaining income, efficiency and strategy. Pure milk has characteristics which are perishable and has short durability, so then came an idea to process pure milk in order to keep Best Cow away from loss and extend the durability. This study aimed to determine added value, incomes, cost efficiency and development strategy of Best Cow cow’s milk processing bussiness on Production Unit of Galur Murni Breeder Cooperation Ajung district Jember Regency. This research was held at Production Unit of Galur Murni Breeder Cooperation at Ajung district, Jember Regency. The method used were descriptive and analytic. Sampling method used were purposive sampling. Data was collected by open interview, observation, and documentation. Data was analized using added value analysis, income analysis, cost efficiency, and SWOT. The results show that: (1) Added value of two products are: (a) added value per liter of raw materials on pure cow’s milk processing into pasteurized milk is Rp 14.180,90 or 54,77% from output value (b) added value per liter of raw materials on pure cow’s milk processing into yogurt is Rp 19.688,41 or 54,69% from output value.; (2) Income of two products are: (a) income of pure cow’s milk processing into pasteurized milk is Rp 3.323.705,56/month (b) income of pure cow’s milk processing into yogurt is Rp 1.969.243,06/month. (3) Cost efficiency of two products are: (a) cost efficiency of pure cow’s milk processing into pasteurized milk efficien with R/C ratio of 1,67 (b) cost efficiency of pure cow’s milk processing into yogurt efficien with R/C ratio of 1,72; (4) Development strategy which has determined is production capacity and expand marketing area with the availability of raw materials